Asset Trading Volume with Dynamically Complete Markets and Heterogeneous Agents - Kenneth L. Judd; Felix Kubler; Karl Schmedders (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2000)
The trading volume of long-lived securities with recursive payoffs, such as equity, is generically zero in infinite-horizon recursive pure exchange Lucas asset models with heterogeneous agents. In equilibrium, there is no portfolio rebalancing of such assets. More generally, the end-of-period portfolio of long- and short-lived securities is constant over time and states in the generic economy. We also present a nonrobust formulation of dynamically complete markets which does have nonzero trading volume in equilibrium. The comparisons show that any theory of asset trading volume will be very sensitive to small changes in model specifications.
Keywords: 330